Continuity in the Development of Judicial Law - Rushanovich Gubaidullin, Aidar; Vitalevna Kurnosova, Valeriya (International Journal of Criminology and Sociology, 2022)
The ongoing changes in the legal map of the world reflect the interaction of legal systems. These processes inevitably affect the scope of activities of the judicial authorities associated with such a phenomenon as judicial law. The authors of the article take a narrow approach to understanding it. It implies the manifestation of judicial law as judicial practice and judicial precedents. The relevance of the topic is due to the fact that the phenomenon of judicial law goes beyond the limits of a single legal family, which implies its comparative legal research. At the same time, an important direction of such activity is the study of the development of this law associated with the processes of continuity. The objective of the study is to identify the concept and features of continuity in the development of judicial law. To do this, the authors formulated the following tasks: identify the concept and signs of continuity within the framework of legal development; disclose the peculiarities of understanding judicial law; determine the characteristic features of continuity in the development of judicial precedents; characterize continuity in the evolution of judicial practice. The conducted research is based on a dialectically understood model of continuity. This assumes the use of a systemic paradigm associated with a constellation of different methods, such as comparative, structural-functional, etc. The results allowed the authors to determine the trends and prospects for the development of judicial law within the framework of certain legal spaces. The authors of the article believe it advisable to use these results in subsequent research on this topic.